Iowa RBA, February 12, 1996 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for February 12, 1996. Highlights of the update include sightings of a Great Grey Owl, Hoary Redpoll, Thayer's Gull and a Varied Thrush. Also included are handwritten notes for the next week's update with sightings of over one hundred Common Redpolls. Epson - sheet feed/flatbed